An Annual Water Budget for Emory Oak Woodlands: An Initial Approximation - Ffolliott, Peter F. (Arizona-Nevada Academy of Science, 2000)
From the Proceedings of the 2000 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - April 15, 2000, University of Arizona, Tucson, Arizona